The changing economy of the Lower Volta, 1954-1967 : a study in the dynamics of rural economic growth - Lawson, Rowena M. (London ; New York : Published for the International African Institute by Oxford University Press, 1972)
This is a study of the Lower Volta (Ghana) in I954 for Sir Robert Jackson's Volta River Project Preparatory Commission focused at a group of relatively large-scale African traders in Accra and Kumasi. It attempts to provide a picture of one area of private economic enterprise by Africans in Ghana, with a view to discovering what factors prevented individual businesses from expanding. The study suggests reluctance to enter into partnerships and delegate authority, as well as a tendency for business interests to be widely dispersed rather than concentrated on building up a single enterprise.
Includes index.
Includes bibliographical references: p. [117]-119.
lje 19/10/2018
Loans
Keywords: Economics; Volta River Valley (Ghana).